(untitled) (Annals of Medical Research, 2023)
Aim: The positive contribution of parental support to children’s cognitive, emotional and social development in early infancy is well known. The aim of this study was to learn the attitudes and opinions of mothers of newborns about supporting development, shared reading, playing games and watching television and to evaluate the factors that may affect these predictions. Materials and Methods: The study was conducted with 154 mothers who applied to İnönü University Faculty of Medicine Developmental Paediatrics outpatient clinic using the "Maternal Attitude Interview Form Regarding Supporting Infant Development". Results: Findings revealed that 136 (88.3%) of mothers planned to reading together, but 88 (57.1%) of them didn’t plan to start before the age of 1 year. There were no baby books in 45.5% and no toys in 30.5% of the houses. A total of 20.1% of the mothers believed that watching television would have a positive impact on development, while 37% planned to allow their children to watch television before the age of 2 years. According to the regression analysis, it was determined that the most significant factor influencing mothers’ intention to begin reading books with their babies before the age of 1 year was higher level of education (p<0.001). Conclusion: The rate of those who don’t plan to read in the early period and those who don’t have baby books and toys in their homes are at a considerable level. Nevertheless, it is promising that the most important factor affecting reading together in the early period is maternal education. It is of great importance that families are informed from pregnancy onwards about the contribution of reading and playing together to development and the negative effects of media tools in early childhood. Increasing the sensitivity of physicians who will follow the mother and the child will ensure the spread of preventive guidance services.